AN INVESTIGATION OF THAI STUDENTS’ ENGLISH LANGUAGE LEARNING STRATEGIES - Agus Trioni Nawa (State Institute for Islamic Studies IAIN of Metro, 2018)
The purpose of this study was to investigate the English language learning strategies implemented by Thai students with the consideration of gender variable. The study employed a descriptive quantitative research design which involved administering questionnaires of rating scale using Oxford, (1990) Strategy Inventory for Language Learning (SILL) to investigate the most frequent language learning strategies from 38 Thai students (15 males and 23 females) of Wahid Hasyim University of Semarang. This study revealed that females showed more strategic (3.34) in learning English than males (2.823). Generally, females showed more frequent use social strategies and males showed more frequent use affective strategies.